1st international business futsal tournament - Tony, Christina (UiTM Sarawak, 2018)
On 21 April 2018, the International Business Club Committee under the leadership of Muhamad Amir Akmal Bin Zahir organised the 1st IBiZ Futsal Tournament. Eighty students from different faculties took part in the event held at FSR Padang Futsal from 8.00 am to 6.30 pm. The objective of this event was to get all the students to meet new friends from different faculties. At the same time, this event helped students to showcase their talent in sports and learn about fair play. In other words, all teams learnt about good teamwork. The tournament started at 10.00 am. Participating in this tournament were ten teams which were Sportivo, An-Nur, Dragon, ManokPuteh, Skyvangers and others. Towards the end of the tournament, all the participants showed great unity and great commitment to their teams.